2010
DOI: 10.1177/1740349911411234
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanics of biologically inspired helical silica nanostructures

Abstract: Diatoms are unicellular algae that exhibit highly intricate, silicified cell walls called frustules. Frustules consist of hierarchical nanostructures composed of amorphous silica and organic protein. Earlier work has suggested diatoms as inspiration for novel molecular sieves, resins, and optical coatings because of their unique mechanical, structural, and optical properties. Here the present authors report studies of the mechanics of helical silica structures inspired by the geometry found in diatom frustules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Investigations into the nanomechanics of nanostructures and nanosprings have been reported using theory and simulations [11][12][13][14] . Some simulations 13 have focused on nanomechanical behavior of amorphous nanosprings because they can explore regimes not fully accessible through experimentation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations into the nanomechanics of nanostructures and nanosprings have been reported using theory and simulations [11][12][13][14] . Some simulations 13 have focused on nanomechanical behavior of amorphous nanosprings because they can explore regimes not fully accessible through experimentation.…”
Section: Introductionmentioning
confidence: 99%
“…Some simulations 13 have focused on nanomechanical behavior of amorphous nanosprings because they can explore regimes not fully accessible through experimentation. Atomistic studies of metallic nanosprings have been reported in literature to investigate the size dependence of elastic properties 15 , and more recently the nanomechanics of helical crystalline silica nanostructures 14 . Experimental testing of nanospring structures has also been performed in different materials such as helical carbon nanostructures and carbon nanocoils [16][17] .…”
Section: Introductionmentioning
confidence: 99%